Using Video as a Replacement or Complement for the Traditional Lecture/Demonstration Method in Agricultural Training in Rural Uganda - Tian Cai; Eric Abbott (Journal of Applied Communications, 2013)
This study explored the effectiveness of video as a tool to either complement or replace existing lecture-demonstration training for small farmer groups. The effectiveness of video in decreasing the knowledge gap among farmers who differ by gender was also evaluated. Quantitative and qualitative data were gathered through a quasi-experiment including a pretest and a posttest design with three experimental groups. Results showed that video could be an effective complement and replacement for the traditional lecture-demonstration training method. Video alone or video plus traditional lecture-demonstration was as effective as traditional training in increasing learning. The training method that included both video and traditional lecture-demonstration was especially effective for groups with relatively low prior knowledge of the training topic. However, video only was not as effective as traditional training or traditional training plus video in decreasing gaps in learning between men and women. Video has advantages in rural areas because it does not require face-to-face presentation by skilled trainers. Video might be an attractive alternative or supplement if the production cost is low enough, or if traditional lecture-demonstration cannot meet the demand for training. Using local actors, shooting video in the local environment and using local languages add to video’s advantages for training purposes. When used to demonstrate a farming technique or practice in a group setting, videos were found to enhance interaction (e.g. discussion and peer learning) among farmers.
Keywords: video training; knowledge gaps; group training; Uganda; pico projector